2020
DOI: 10.1111/jsr.13135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sleep modulation during pregnancy in the mother and offspring: Evidences from preclinical research

Abstract: Disturbed sleep during gestation may lead to adverse outcomes for both mother and child. Animal research plays an important role in providing insights into this research field by enabling ethical and methodological requirements that are not possible in humans. Here, we present an overview and discuss the main research findings related to the effects of prenatal sleep deprivation in animal models. Using systematic review approaches, we retrieved 42 articles dealing with some type of sleep alteration.The most fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 94 publications
0
27
0
1
Order By: Relevance
“…Animal studies have shown that the circadian rhythm is affected by maternal life rhythms via endogenous substances such as melatonin 14 , 15 . Animal studies have also reported that exposure to sleep deprivation or artificial disappearance of light–dark cycle during pregnancy affects the offspring’s circadian rhythm abnormality and abnormal behavioral pattern 16 , 17 . In this study, mother’s short sleep and late bedtime were associated with the offspring’s sleeping problems, in part, because of the influence of maternal life rhythm during the fetal period.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown that the circadian rhythm is affected by maternal life rhythms via endogenous substances such as melatonin 14 , 15 . Animal studies have also reported that exposure to sleep deprivation or artificial disappearance of light–dark cycle during pregnancy affects the offspring’s circadian rhythm abnormality and abnormal behavioral pattern 16 , 17 . In this study, mother’s short sleep and late bedtime were associated with the offspring’s sleeping problems, in part, because of the influence of maternal life rhythm during the fetal period.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disorders have been associated with the occurrence of metabolic [ 27 ], cardiovascular [ 28 ], and mood and cognitive diseases [ 29 ], as well as tumor aggressiveness and poor prognosis in cancer [ 30 ]. Moreover, gestational sleep disturbances can lead to adverse outcomes for both the mother and the child [ 31 ].…”
Section: Sleep Disorders and Associated Morbidities Need For Precision Medicinementioning
confidence: 99%
“…In the study of Kovac et al [ 127 ], they found a modest interaction between a single nucleotide polymorphism in PER3 and triglycerides on the association with preterm birth. Sleep disturbances during pregnancy might be detrimental to both mother and offspring by promoting increased risk at the behavioural, electrophysiological, metabolic and epigenetic levels and are associated with some hormonal changes, including: increased progesterone levels (causing fatigue and daytime sleepiness), increased estrogen levels (which selectively decrease REM sleep activation in the preoptic ventrolateral area), alterations in cortisol secretion (which decreases REM sleep and increases slow wave sleep), alterations in prolactin levels (which exacerbates slow wave sleep), alterations in growth hormone levels (associated with the initiation and maintenance of slow wave sleep) and these changes play an important role in the growth and development of the fetus [ 21 , 128 ]. Although these changes obey a normal physiological process in pregnant women, they can generate complications, especially when obesity occurs, since the prevalence of sleep apnea is higher.…”
Section: Sleep and Metabolic Programmingmentioning
confidence: 99%
“…On the other hand, physiological changes that occur during pregnancy, are associated with changes in sleep architecture. These changes can cause negative effects on the health of the mother and her offspring both at a psychological level, as well as at a metabolic and epigenetic level [ 21 ]. Also, sleep duration and quality have an impact in dietary patterns which has a direct impact on the offspring’s health outcomes [ 22 ].…”
Section: Introductionmentioning
confidence: 99%